Legal Protection for Girls in the Distribution of Inheritance Based on Batak Toba Customary Law (In Janjiraja Village, Samosir Regency) - Roma Cita Sibatuara; Martono Anggusti; Roida Nababan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Batak Toba customary law adheres to a patrilineal inheritance system, where male children are the primary heirs of family assets, while female children only receive symbolic portions in the form of gifts or jambar. This study aims to examine the legal protection for female children in inheritance distribution in Janjiraja Village, Samosir Regency, focusing on customary practices and gender equality. The research uses a juridical-sociological method, combining legal analysis with observations of the implementation of customs in the community. The findings show that although there are protective mechanisms such as parjambar and family discussions, their implementation is hindered by the patrilineal culture, lack of understanding of national law, and social pressures from the customary environment. However, there is a shift in attitudes among the younger generation, who are more supportive of gender equality, influenced by education, urbanization, and national legal frameworks. This study concludes that legal protection for female children in Batak Toba inheritance requires an approach that combines customary values with gender equality principles, leading to a more equitable distribution of family inheritance.